Investigating immunocompetence in Aseel, Kadaknath and White Leghorn chicken - KOKATE, LAXMIKANT SAMBHAJI; KUMAR, SANJEEV; RAHIM, ABDUL; DAS, ANANTA KUMAR (The Indian Journal of Animal Sciences, 2017)
The study aimed to investigate immunocompetence in Aseel, Kadaknath and IWH line of White Leghorn chicken maintained at this institute. Five to six weeks aged pedigreed 75, 55 and 100 chicks progenies of 8, 8 and 20 sires of these respective genotypes were immunized against 1% (v/v) SRBC suspension. Five dpi sera were analyzed through haemagglutination (HA) test to assess humoral immune response. Serum lysozyme and immunoglobulin-G (IgG) concentrations were assessed through agarose lysoplate and single radial immunodiffusion assay, respectively. The data were analyzed by least squares analysis of variance. The estimated corresponding means of HA titre, serum lysozyme and serum IgG concentrations were 10.84±0.18, 21.28±0.78 μg/ml and 24.23±2.05 μg/μl in Aseel, 11.62±0.21, 16.91±0.93 μg/ml and 15.70±2.44 μg/μl in Kadaknath, and 11.94±0.15, 9.42±0.68 μg/mland 10.27±1.79 μg/μlin IWH line of White Leghorn chicken. The estimates significantly varied among the three genotypes. The HA titre mean was higher in IWH line of WLH followed by Kadaknath and Aseel chicken; whereas serum lysozyme and serum IgG concentration means were higher in Aseel followed by Kadaknath and IWH line. Sire within genotype or sire and sex of the birds had nonsignificant effect on the traits. This information could be important while selecting birds for improvement in general immune responsiveness and the high immunocompetence in Aseel and Kadaknath might be exploited by their selective introgression in high productive but less immunocompetent chicken germplasms.